Escherichia coli brain abscess in a twin pair associated with TLR4 gene mutation. Issue 4 (5th August 2013) - Erdemir, Aydin; Kahramaner, Zelal; Cosar, Hese; Turkoglu, Ebru; Sutcuoglu, Sumer; Uygun, Dilara Kocacik; Yegin, Olcay; Berdeli, Afig; Ozer, Esra Arun
Abstract: Brain abscesses are uncommon complications of bacterial meningitis or sepsis in neonates and infants. The causative pathogens of brain abscess in newborns are various. Of those, Escherichia coli is rarely seen as a pathogen in brain abscess at this age. Herein we reported brain abscesses in twin infants caused by E. coli sepsis. Interestingly, genetic analysis identified heterozygous Toll‐like receptor 4 ( TLR4 ) gene mutation in the twins. Because TLR plays an important role in the natural response to bacterial products and initiates specific immune response against these pathogens, this may explain the development of brain abscess in the present case.